Post-discharge interventions to enhance coping skills for survivors of stroke and their caregivers: a scoping review protocol. Issue 2 (18th February 2020) - Schwertfeger, Julie Lynn; Thuente, Lori; Hung, Paul; Larson, Sandra Louise
ABSTRACT: Objective: This scoping review aims to map the use of post-discharge interventions to enhance coping skills for adult stroke survivors and their informal caregivers. Introduction: Evidence shows that when stroke survivors and their informal caregivers are provided with post-discharge coping training, their outcomes improve. There is also evidence that healthcare providers currently focus on medication compliance and deliver little to no instruction on post-discharge coping interventions. As a result, more than 40% of stroke survivors and informal caregivers report a lack of awareness and access to community-based coping training once discharged from the hospital setting. Inclusion criteria: This scoping review will map the delivery modes, intervention types, locations, leadership and settings of current coping interventions for community-dwelling adults 18 years or older living with the effects of stroke and their informal caregivers. This review will be restricted to studies published in English that include interventions that are not reimbursed as part of United States healthcare coverage. Methods: The search will include CINAHL, Cochrane Library, Embase, JBI Evidence Synthesis, MEDLINE, PEDro, PLoS, PsycINFO, and Web of Science. In addition, smaller health-related databases, stroke and rehabilitation journals, gray literature and stakeholder organization websites will be searched. A three-step search strategy will be utilized, including use of citation software to manage search results and de-duplication, abstract review and full-text review by two reviewers. Details of included studies will then be imported into information management software. The resulting map will be displayed in tabular form along with a narrative summary.